VOIP for Telerehabilitation: A Risk Analysis for Privacy, Security and HIPAA Compliance: Part II - Watzlaf, Valerie J.M.; Moeini, Sohrab; Matusow, Laura; Firouzan, Patti (International Journal of Telerehabilitation, 2011)
In a previous publication the authors developed a privacy and security checklist to evaluate Voice over the Internet Protocol (VoIP) videoconferencing software used between patients and therapists to provide telerehabilitation (TR) therapy. In this paper, the privacy and security checklist that was previously developed is used to perform a risk analysis of the top ten VoIP videoconferencing software to determine if their policies provide answers to the privacy and security checklist. Sixty percent of the companies claimed they do not listen into video-therapy calls unless maintenance is needed. Only 50% of the companies assessed use some form of encryption, and some did not specify what type of encryption was used. Seventy percent of the companies assessed did not specify any form of auditing on their servers. Statistically significant differences across company websites were found for sharing information outside of the country (p=0.010), encryption (p=0.006), and security evaluation (p=0.005). Healthcare providers considering use of VoIP software for TR services may consider using this privacy and security checklist before deciding to incorporate a VoIP software system for TR. Other videoconferencing software that is specific for TR with strong encryption, good access controls, and hardware that meets privacy and security standards should be considered for use with TR. Keywords: Voice over the Internet Protocol (VOIP), telerehabilitation, HIPAA, privacy, security, evaluation